FRAMEWORK FOR ENGLISH LANGUAGE LEARNING BASED ON SABUNESE FOLKLORE AS A MEANS FOR ENRICHING LEXICAL KNOWLEDGE RELATED TO SABUNESE TRADITIONAL ECONOMIC SYSTEMS - Josua Bire; Fransiskus Bustan; Agustinus Semiun (Postgraduate School, Universitas Nusa Cendana, 2019)
This research aims to develop a framework for English language learning based on Sabunese folklore as a means for enriching lexical knowledge related to traditional economic systems within the Sabunese culture. Theoretical framework on which this research is based on is applied cultural linguistic which empowers local cultural products and practices of Sabunese people in form of folklores as the basis for modelling English language learning based on local culture. This research is that of a descriptive study which blends analysis and its application in form of framework development. Research results develop the English language learning framework based on Sabunese folklore which functions as an approach to enrichment of lexical knowledge related to traditional economic systems which encompasses agriculture, farming, and trading systems. The framework development is that of a single entry – multiple outputs, as the model provides several outputs besides enrichment approach to lexical knowledge related to traditional economic systems embedded within the Sabunese culture as the main focus of this research. The developed framework is applicable to other fields with necessary modifications depending on specific aims and context.